THE PARADISE OF PATRIARCHY: AMBROSIASTER ON WOMAN AS (NOT) GOD'S IMAGE - Hunter, David G. (The journal of theological studies, 1992)
DAVID G. HUNTER; THE PARADISE OF PATRIARCHY: AMBROSIASTER ON WOMAN AS (NOT) GOD'S IMAGE*, The Journal of Theological Studies, Volume 43, Issue 2, 1 October 1992